2011
DOI: 10.1097/jto.0b013e31820db209
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Gene Alterations in a Norwegian Cohort of Lung Cancer Patients Selected for Surgery

Abstract: The frequency of EGFR mutations is lower in our cohort than among Asian lung cancer patients and present in both men and women and smokers and never-smokers. However, the frequency is significantly higher among women and never-smokers and among patients with adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 10 publications
6
34
0
2
Order By: Relevance
“…These were investigations on resection specimens, an earlier one from Italy with a 4.5% occurrence [15], and a recent one from Norway (6.6% [16]). In another of our series on resection specimens, the frequency was lower as well at 7.0% (personal communication C. Dooms).…”
Section: Resultsmentioning
confidence: 99%
“…These were investigations on resection specimens, an earlier one from Italy with a 4.5% occurrence [15], and a recent one from Norway (6.6% [16]). In another of our series on resection specimens, the frequency was lower as well at 7.0% (personal communication C. Dooms).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the EGFR-TKI-sensitive mutation was high in AD in an Asian population, but was low in Caucasians [50][51][52][53][54]. The full range of genetic factors involved in the susceptibility to lung cancer are still unclear, but some studies have suggested an association between family history and the risk of lung cancer, especially in the case of AD [55].…”
Section: Differences In Lung Cancer Among Ethnicitiesmentioning
confidence: 99%
“…Several other EGFR mutations have been reported, but their clinical significance is yet unknown. Mutation rate in adenocarcinomas in East Asian patients are 20-50% 9 and 5-15% in Western European patients depending on whether selected 9 or unselected [10][11][12][13] patients are tested.…”
mentioning
confidence: 99%